Pemberdayaan Masyarakat Penambang Emas di Kalimantan Tengah melalui Inkubasi Bisnis Berbasis Pertanian dan Peternakan Terpadu - Liswara Neneng; Ria Anjalani; Dewi Saraswati; Stevin Carolius Angga; Syarpin Syarpin (FKIP Universitas Palangka Raya, 2022)
Many areas in Central Kalimantan have a lot of small-scale gold mining activities (illegal mining), involved thousands of gold miners. These gold mining activities had caused extensive damage to the landscape, both on land and in waters. This activities carried out aim to; (1) Developing an integrated form of business incubation in agriculture and animal husbandry for gold mining communities in 3 villages in Central Kalimantan; (2) Conduct socialization, training, and assistance to the gold mining community in cultivating chickens intensively, diversifying livestock production, and carrying out integrated agriculture in a sustainable manner; (3) Fostering productive business units from upstream to downstream in integrated agriculture, through the support of infrastructure, purchase of tools and materials, to find prospective market networks through the implementation of post-harvest processing and appropriate marketing strategies. These activities were carried out in 3 (three) villages, namely, Tuwung Village, Sigi Village, and Marang Sub-District, from September to December 2022. The results of the activity showed an increase in the participants' knowledge regarding the dangers of mercury pollution and alternative types of businesses that were more productive and environmentally friendly. The skills of the miners have also increased, in terms of chicken cultivation, maggot cultivation, and post-harvest processing and also marketing. This activity is also able to support the economy of gold miners, which is obtained from the sale of 4 main products, namely chicken products, magot products, agricultural commodities, and livestock manure compost. On average, 60% of miners stated that they were willing to shift their jobs from gold miners to workers in integrated agriculture and animal husbandry.